2008
DOI: 10.1111/j.1399-302x.2008.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors involved in the T helper type 1 and type 2 cell commitment and osteoclast regulation in inflammatory apical diseases

Abstract: Our results showed a predominance of osteoclast activity in granulomas that was correlated with the Th1 response. The concomitant expression of Treg cell markers suggests a possible suppression of the Th1 response in granulomas. On the other hand, in cysts the Th2 activity is augmented. The mechanisms of periradicular lesion development are still not fully understood but the imbalance of immune and osteoclastic cell activity in cysts and granulomas seems to be critically regulated by Treg cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
2
17

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(150 citation statements)
references
References 56 publications
9
122
2
17
Order By: Relevance
“…In phase 2, the full-text of 18 studies were retrieved and evaluated. Of those, only eight 14,15,16,17,18,19,20,21 met the eligibility criteria. No additional study was identified in the reference lists of the included articles and in the grey literature.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…In phase 2, the full-text of 18 studies were retrieved and evaluated. Of those, only eight 14,15,16,17,18,19,20,21 met the eligibility criteria. No additional study was identified in the reference lists of the included articles and in the grey literature.…”
Section: Study Selectionmentioning
confidence: 99%
“…14,15,18,21 All studies involved human periapical lesion fragments. Samples of six articles 14,15,18,19,20,21 were obtained directly through surgery and samples of the other two studies were obtained through institutional archives collected from previous surgical procedures.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the symptomatic PLs are characterized by the upregulation of adhesive molecules, chemotactic factors (3), T helper (Th)1 and Th17 cytokines as well as bone resorptive cytokines such as interleukin (IL)-1, IL-6, and tumour necrosis factor (TNF)-α (2,4). On the other hand, the generation of asymptomatic PLs is followed by the Th2 immune response, which promotes PL chronicity with restriction of inflammation (5). The predominant cytokines in chronic PLs are IL-10 and transforming growth factor (TGF)-β, which are involved in healing and regression of the inflammation within PLs (2).…”
Section: Introductionmentioning
confidence: 99%